# Question:how can i solve nonlinear equations ?

## Question:how can i solve nonlinear equations ?

Maple

how can i solve these two massive nonlinear equations ? and by which way ?

the 1st is:-

n[-(2*(2*n+1))*e^(-2*`λa`(2*n+1))+(3*n+2)*e^(-`λa`(3*n+2))+(3*n+1)*e^(-`λa`(3*n+1))-(2*n+1)*e^(-`λa`(2*n+1))]-(sum([-(2*(n+i+1))*e^(-2*`λa`(2*n+i+1))+(2*n+i+2)*e^(-`λa`(2*n+i+2))+(2*n+i+1)*e^(-`λa`(2*n+i+1))-(2*n+1)*e^(-`λa`(2*n+1))], i = 1 .. n-1))-k(2*n+1)*e^(-`λa`(2*n+1))*[e^(-`λb`(2*k+1))-e^(-`λb`(k+1))-e^(-`λbk`)+1]+(2*n+1)*e^(-`λa`(2*n+1))*(sum([e^(-`λb`(2*j+1))-e^(-`λb`(j+1))-e^(-`λbj`)+1], j = 1 .. k-1))-(2*`λne`^(-2*`λan`)+2*lambda(n+1)*e^(-2*`λa`(n+1))-2*lambda(2*n+1)*e^(-2*`λa`(2*n+1)))*[n[e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1))]-(sum([e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1))+e^(-`λa`(2*n+1))], i = 1 .. n-1))+ke^(-`λa`(2*n+1))*[e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1]-e^(-`λa`(2*n+1))*(sum([e^(-`λb`(2*j+1))-e^`λb`(j+1)-e^(-`λjb`)+1], j = 1 .. k-1))]/(1-e^(-2*`λa`(n+1)))(1-e^(-2*`λan`)) = 0

the 2nd is:-

n[e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1))]-(sum([e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1))+e^(-`λa`(2*n+1))], i = 1 .. n-1))+ke^(-`λa`(2*n+1))*[e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1]-e^(-`λa`(2*n+1))*(sum([e^(-`λb`(2*j+1))-e^(-`λb`(j+1))-e^(-`λbj`)+1], j = 1 .. k-1))+be^(-`λa`(2*n+1))*[k[-lambda(2*k+1)*e^(-`λb`(2*k+1))-lambda(k+1)*e^(-`λb`(k+1))+`λke`^(-`λbk`)]-(sum([-lambda(2*j+1)*e^(-`λb`(2*j+1))+lambda(j+1)*e^(-`λb`(j+1))+`λje`^(-`λbj`)], j = 1 .. k-1))] = 0

i want (a,b) .

plz help. thanks

﻿